Integrating indigenous and modern water supply systems in rural South Africa - Ngema, N. N.; Mbanga, S. L.; Adeniran, A. A.; Kabundu, E. (Frontiers in Water, 2024)
Water is essential for human survival, economic growth, and environmental sustainability. However, rural South Africa faces ongoing challenges in delivering reliable and clean water due to infrastructural inadequacies, climate variability, and historical disparities. Addressing these water supply issues is critical for reducing poverty, improving health outcomes, and fostering sustainable development in rural areas. This study utilises a mixed-methods approach within a positivist framework, collecting data through document analysis, self-administered surveys, and structured interviews with various stakeholders across four rural settlements in the Joe Gqabi and Gert Sibande District Municipalities. The primary aims are to evaluate water accessibility and reliability, examine the impact of water scarcity on poverty, investigate the availability of water infrastructure, and assess the effects of water supply on health and education. Findings indicate that deficient water infrastructure and intermittent supply significantly disrupt daily life, educational access, and healthcare services. Health risks due to contaminated water were prevalent, leading to waterborne diseases. Socio-economic impacts included exacerbated poverty, with particular challenges for female students in maintaining menstrual hygiene due to inconsistent water availability. The study proposes a sustainability model that integrates indigenous practices, such as rainwater harvesting and groundwater recharge, with modern water management technologies. This model, customised to local needs, underscores the importance of increased investment, integrated planning, and enhanced capacity-building in rural water management. By combining traditional and modern approaches, this model aims to improve water reliability, promote health, and support economic resilience in rural settlements.